P206 Audit of compliance to guidelines of down syndrome(DS) management in nicu of university maternity hospital limerick(UMHL). (June 2019) - Bakar, Muhammad Abu; Sreenan, Con
Abstract : Background: Children with Down syndrome have multiple malformations because of the presence of extra genetic material from chromosome 21(1). The guidelines is designed to help the pediatrician to care for children with Down syndrome and their families(1). Objective: To assess compliance to guidelines for management of Down Syndrome babies admitted in NICU of UMHL in 2017. Methodology: Retrospective study on DS babies admitted to NICU of UMHL in 2017 by collecting data from hospital inpatient enquiry system(HIPE) of UMHL. Different variables were studied including admission examination, cardiac assessment, DS centile chart, karyotype request, guthrie card, full blood count(FBC), cardio referral, typed discharge letter, ophthalmology assessment, hearing assessment, medical social worker(MSW) referral, physiotherapy referral, early intervention team(EIT) referral, information leaflet to parents, DS registry consent and follow up. Standard: Medical management guidelines for DS developed by The National Children, s Hospital, Tallaght, Dublin and updated on 30 th Sep 2009. Results: Total 10 babies listed with DS admitted in NICU in 2017. 40%(n=4) were excluded because of normal karyotype and referral to other hospital. Study was conducted on remaining 60%(n=6) babies which showed 100% compliance to guidelines for cardiac assessment, karyotype request, FBC, cardio referral, EIT referral, information leaflets to parents and follow up. 17%(n=1) failed to comply with guidelines for admission examination, DS centile chart, Guthrie card, typed discharge letter, ophthalmology assessment, hearing assessment, and physiotherapy referral. MSW referral was not sent in 67%(n=4) and failed to get DS registry consent in 100%(n=6) babies. Conclusion: Medical social worker referral and consent for DS registry were the most deficient aspects of its management. Further, compliance is also required in admission examination, DS centile chart, Guthrie card, typed discharge letter, ophthalmology assessment, hearing assessment, and physiotherapy referral. References: Health Supervision for Children With Down Syndrome: American Academy Of Pediatrics 2001; Vol 107/Issue 2